President Johnson's war on poverty : rhetoric and history - Zarefsky, David (University of Alabama Press, 1986)
Normal0falsefalsefalseMicrosoftInternetExplorer4 In January 1964, in his first State of the Union address, President Lyndon Johnson announced a declaration of "unconditional war" on poverty. By the end of the year the Economic Opportunity Act became law. The War on Poverty illustrates the interweaving of rhetorical and historical forces in shaping public policy. Zarefsky suggest that an important problem in the War on Poverty lay in its discourse. He assumes that language plays a central role in the formulation of social policy by shaping the context within which people view the social worl.